Investigation of the main mechanical characteristics of plastics for three-dimensional printing of machine parts models. Issue 5 (March 2021) - Dorodov, P V; Kasatkin, V V; Kasatkina, N Y; Petrov, V A; Litvinyuk, A A
Abstract: Today, new methods of manufacturing complex parts using three-dimensional printing are being introduced in engineering, including in the mechanical engineering of agricultural machinery. This technique is also used in the design of agricultural machinery at the stage of physical modeling of their structures to determine certain properties of the product as a whole and its individual parts (details) on the corresponding models. Physical modeling is used when it is difficult to perform full-scale tests of the product, as well as for economic reasons. The necessary conditions for physical modeling are the geometric and physical similarity of the model and kind. The presence of such proportionality allows us to recalculate the experimental results obtained for the model in kind by multiplying each of the determined values by a constant multiplier for all values of this dimension – the similarity coefficient. However, to study the physical characteristics of a product, it is necessary to take into account the mechanical properties of the material of its model. From various sources, you can find the main mechanical characteristics of plastic threads or samples made on a 3-D printer. Their values vary greatly depending on the model manufacturing technology. The paper presents the results of a study of the physical and mechanical properties of polylactide (PLA) and polyethylene tereflatate (PET-G), which are used in the manufacture of parts by three-dimensional printing. The specific strength of polymers was respectively: for PLA 65.6…12.2 kPa·m 3 /kg, for PET-G 36.7…95.4 kPa·m 3 /kg. Specific plasticity for PLA is equal to 60., 3 %· cm 3 /kg, for PET-G – 468.2 %· cm 3 /kg. The specific plasticity for PLA is 608.3 %· cm 3 /kg, for PET-G – 468.2 %· cm 3 /kg. Mechanical properties are investigated and the obtained mechanical characteristics must be taken into account when calculating and physically modeling plastic products for three-dimensional printing.